Design of a 3D Virtual World to Implement a Logical Access Control Mechanism Based on Fingerprints - Bader, Samira; Ben Amara, Najoua Essoukri (2017 IEEE/ACS 14th International Conference on Computer Systems and Applications (AICCSA), 2017)
3D virtual worlds have technologically emerged as platforms able to support millions of users to interact with each other, sharing information on business, education, social science, news and cutting-edge technologies. Despite their maturity, they are subject to cybercrimes due to the lack of an efficient access control mechanism. Technically, it is l essential to install a biometric access control solution to secure these virtual spaces. Actually, virtual world platforms are only equipped with classical password-based authentication mechanism. The implementation of new a logical access control procedure in publicly accessible virtual worlds is closely dependent on the characteristics of the virtual world platform. In this study, we put forward a methodology to design a virtual world platform for the implementation of a biometrical access control mechanisms. For virtual world building, we use as software a set of 3D tools and the Unreal Engine, which is a complete suite of 3D game and space development tools. To implement the access control application, we develop a centralized biometric authentication module based on fingerprints.